Impact of pulsed electromagnetic field on mixed incontinence in parous women a prospective randomized study - Eman A. Elhosary; Lamyaa A. Fergany; Marwa A. Mohamed (IMR Press, 2022)
Background: This study was conducted to determine the impact of a pulsed electromagnetic field (PEMF) on mixed incontinence. This condition can have a significant impact on women's quality of life and social relationships. Methods: Parous females (n = 40) with mixed incontinence were randomly assigned to one of two groups. Group A received PEMF and pelvic floor muscle training in addition to general advice for 12 sessions. Group B received the same program but without PEMF. Pelvic floor muscle strength and the severity of urinary incontinence were assessed using a perineometer and the incontinence symptom severity index (ISSI), respectively. Results: Within groups comparison show statistically significant improvement in priniomter and severity index after treatment in comparison to pre treatment values. Between groups comparison after treatment showed better improvement in group A (p < 0.05) in pelvic floor muscle strength and a significant decrease (p < 0.05) in the severity of urinary incontinence compared to group B. Conclusions: PEMF combined with pelvic floor muscle training is an effective, convenient, and acceptable way to manage mixed incontinence.